Correlation of Elbow Carrying Angle with Height and Forearm Length among Bangladeshi Adolescent (IAHS Medical Journal, 2024)
Background: Carrying angle is a medial acute angle between median axis of the upper arm with the fully extended and supinated forearm. It plays a vital role in carrying objects and keeps upper extremity away from the pelvis during walking and disappears when the forearm is pronated and flexed. It increases with age from childhood to adolescent and is greater in female and in dominant arm; also differs with race, ethnicity and number of anthropometric body parameters. Present study was designed to evaluate the carrying angle in normal adolescents of Bangladesh and to see its correlation with height and forearm length in both sexes.Materials and methods: This cross-sectional analytical study was conducted in the Department of Anatomy,Chittagong Medical College, Chattogram upon 100 male and 100 female adolescents of 10-19 years. After getting permission from the ethical review committee, carrying angle, height and forearm length of the participants were measured by standard method. Recorded data were analyzed by using SPSS version 25. For statistical analysis Pearson’s correlation test was done. p-value was considered significant if it was